Ensaio clínico randomizado multicêntrico para avaliar a eficácia de injeções intravítreas de bevacizumabe, triancinolona ou de sua combinação no tratamento do edema macular diabético - Oliveira Neto, Hermelino Lopes de [UNIFESP] (2015)
In diabetic patients, it is estimated that the risk of blindness is twenty times higher than the normal population and approximately 19% of blindness in the world are caused by diabetes mellitus (DM). In Brazil, diabetic retinopathy (DR), a specific microvascular complication, is among the leading causes of irreversible blindness, affecting 7.6% of the population according to the Ministry of Health, and this disease accounts for 4.6% of severe visual impairments. The diabetic macular edema (EMD) is the primary mechanism for vision lossin patients with non-proliferative DR. It arises due to secondary formation of micro aneurysms, changes in the blood-retinal barrier, increasedinflammation and angigenic factors that promote increase in thevascular permeability abd consequent leakage of fluid and lipids to the retina. The EMD treatment includes laser photocoagulation, intravitreal injection of anti-angiogenic drugs or steroids.The aim of this study was to evaluate and compare the efficacy and adverse effects of intravitreous injections of bevacizumab, triancinolone or their combination in the treatment of clinically significant diabetic macular edema through tests of visual acuity and IOP measurements and central macular thickness. This study included142 patients with diabetic retinopathy and clinically significant macular edema from eight cities. It is a randomized, multicenter and masked study. Patients underwent ophthalmologic examination and optical coherence tomography (OCT). Afterwards they were divided into three treatment groups: (1) Bevacizumab-1.25mg /0.05ml; (2) triamcinolone-4mg /0.1ml; (3) Bevacizumab+triancinolone. The obtained average age was 58.8 years for the BEVACIZUMABE group, 57.1 years for the TRIANCINOLONE group and 61years for BEVACIZUMABE+TRIANCINOLONE group(p =0.716). We observed statistically significant improvement in visual acuity (>4lines) in all groups, comparing the results of week 24 with the baseline visit. At week 24 there was no significant difference in the visual acuity between the 3 groups (p =0.436). It was observed reduction in macular thickness in all thegroups (BEVACIZUMABE=103?m, TRIANCINOLONE=160 micrometres BEVACIZUMABE TRIANCINOLONE+=125um), and the TRIANCINOLONE group showed significantly less thick(247 microns) than the bevacizumab group (287 microns). In all groups, there was an IOP increase, and the TRIANCINOLONE group had higher mean value of IOP throughout the study period (18 mmHg) .The average number of injections was higher in the BEVACIZUMABE group (3.2 injections), followed by BEVACIZUMABE+TRIAMCINOLONE (2.4 injections) and TRIANCINOLONA (2.1injections) group.In this investigation no severe adverse event was observed. At the end of the study, there was no significant difference between the groups regarding the visual acuity, intraocular pressure and central macular thickness.